Eosinophilic Esophagitis in Children and Adolescents with Abdominal Pain: Comparison with EoE-Dysphagia and Functional Abdominal Pain - Thirumazhisai Gunasekaran; Gautham Prabhakar; Alan Schwartz; Kiranmai Gorla; Sandeep Gupta; James Berman (Canadian Journal of Gastroenterology and Hepatology)
Aim. Compare EoE-AP with EoE-D for clinical, endoscopy (EGD), histology and outcomes and also with FAP-N. Method. Symptoms, physical findings, EGD, histology, symptom scores, and treatments were recorded for the three groups. Cluster analysis was done. Results. Dysphagia and abdominal pain were different in numbers but not statistically significant between EoE-AP and EoE-D. EGD, linear furrows, white exudates were more in the EoE-D and both combined were significant (p<0.05). EoE-D, peak and mean eosinophils (p  0.06) and eosinophilic micro abscesses (p  0.001) were higher. Follow-Up. Based on single symptom, EoE-AP had 30% (p  0.25) improvement, EoE-D 86% (p<0.001) and similar with composite score (p  0.57 and <0.001, resp.). Patients who had follow-up, EGD: 42.8% with EoE-AP and 77.8% with EoE-D, showed single symptom improvement and the eosinophil count fell from 38.5/34.6 (peak and mean) to 31.2/30.4 (p  0.70) and from 43.6/40.8 to 25.2/22.8 (p<0.001), respectively. FAP-N patients had similar symptom improvement like EoE-D. Cluster Analysis. EoE-AP and FAP-N were similar in clinical features and response to treatment, but EoE-D was distinctly different from EoE-AP and FAP-N. Conclusion. Our study demonstrates that EoE-AP and EoE-D have different histology and outcomes. In addition, EoE-AP has clinical features similar to the FAP-N group.